An MR Damper Parametric Model with luz(...) Projection Function and Its Application in an Open-loop Force Tracking Control System - Raymundus Lullus Lambang Govinda Hidajat; Fitrian Imaduddin; Budi Santoso; Irianto Irianto; Azma Putra; Ubaidillah Ubaidillah (Universitas Sebelas Maret, 2024)
This research discusses a parametric model with a luz(...) projection function for an outer bypass Magnetorheological (MR) damper with a meandering type valve and its application in an open-loop force tracking control system. This parametric model with the luz(…) projection function has been developed previously. The MR damper force can be controlled with open-loop force as a standard control strategy. Research on the performance of the MR damper model in open-loop control systems usually uses non-parametric models. Thus, the novelty of this research is that it uses a parametric model, i.e., the model of the luz(...) projection function as the model of the outer bypass MR damper with a meandering type valve. The proposed open-loop control system uses an inverse model that produces an electric current according to the desired force. The force tracking control scheme was realized with computer simulations using a state space approach. These simulation results show that the model with the luz(…) projection function can efficiently and accurately track the desired force in an open-loop force-tracking control system. The desired force is sinusoidal, square, and sawtooth waveform. Relative Error (RE) of 0.000, 0.0123, and 0.0563, respectively, are achieved.